Interleukin-31 promotes pathogenic mechanisms underlying skin and lung fibrosis in scleroderma - Yaseen, Bodoor; Lopez, Henry; Taki, Zeinab; Zafar, Sara; Rosario, Henrique; Abdi, Bahja Ahmed; Vigneswaran, Shivanee; Xing, Fiona; Arumalla, Nikita; Black, Simon; Ahmad, Sara; Kumar, Kimti; et al. (Rheumatology (Oxford, England), 2020)
Cytokines released by infiltrating T cells may promote mechanisms leading to fibrosis in scleroderma. The aim of this study was to investigate the role of the Th2 cytokine IL-31, and its receptor IL-31RA, in scleroderma skin and lung fibrosis. IL-31 was measured by ELISA of plasma, and by immunochemistry of fibrotic skin and lung tissue of scleroderma patients. The receptor, IL-31RA, was assayed by qPCR of tissue resident cells. Next-generation sequencing was used to profile the responses of normal skin fibroblasts to IL-31. In wild-type Balb/c mice, IL-31 was administered by subcutaneous mini pump, with or without additional TGFβ, and the fibrotic reaction measured by histology and ELISA of plasma. IL-31 was present at high levels in plasma and fibrotic skin and lung lesions in a subset of scleroderma patients, and the receptor overexpressed by downstream cells relevant to the disease process, including skin and lung fibroblasts, through loss of epigenetic regulation by miR326. In skin fibroblasts, IL-31 induced next generation sequencing profiles associated with cellular growth and proliferation, anaerobic metabolism and mineralization, and negatively associated with angiogenesis and vascular repair, as well as promoting phenotype changes including migration and collagen protein release via pSTAT3, resembling the activation state in the disease. In mice, IL-31 induced skin and lung fibrosis. No synergy was seen with TGFβ, which supressed IL-31RA. IL-31/IL-31RA is confirmed as a candidate pro-fibrotic pathway, which may contribute to skin and lung fibrosis in a subset of scleroderma patients.